Perspectives on snakebite envenoming care needs across different sociocultural contexts and health systems: A comparative qualitative analysis among US and Brazilian health providers. (March 2023) - Strand, Eleanor; Murta, Felipe; Tupetz, Anna; Barcenas, Loren; Phillips, Ashley J.; Farias, Altair Seabra; Santos, Alícia Cacau; Rocha, Gisele dos Santos; Staton, Catherine A.; Ramos, Flávia Regina; Machado, Vinícius Azevedo; Wen, Fan Hui; et al.
Abstract: With the advancements in therapeutics and available treatment options, almost all deaths and permanent disabilities from snakebite envenoming (SBE) are preventable. The challenge lies in implementing these evidence-based treatments and practices across different settings and populations. This study aims to compare data on provider perceptions of SBE care across health systems and cultural contexts to inform potential implementation science approaches. We hypothesize different health systems and cultural contexts will influence specific perceived needs to provide adequate snakebite care within central tenets of care delivery (e.g., cost, access, human resources). We previously conducted exploratory descriptive studies in the US and Brazil in order to understand the experience, knowledge, and perceptions of health professionals treating SBE. In the US, in-depth interviews were performed with emergency physicians from January 2020 to March 2020. In BR, focus group discussions were conducted with health professionals from community health centers at the end of June 2021. The focus group discussions (BR) were originally analyzed through an inductive thematic analysis approach. We conducted a secondary qualitative analysis in which this codebook was then applied to the interviews (US) in a deductive content analysis. The analysis concluded in August 2022. Brazil participants were physicians (n=5) or nurses (n=20) from three municipalities in the State of Amazonas with an average of three years of professional experience. US participants were emergency physicians (n=16) with an average of 15 years of professional experience. Four main themes emerged: 1) barriers to adequate care on the patient and/or community side and 2) on the health system side, 3) perceived considerations for how to address SBE, and 4) identified needs for improving care. There were 25 subthemes within the four themes. These subthemes were largely the same across the Brazil and US data, but the rationale and content within each shared subtheme varied significantly. For example, the subtheme "role of health professionals in improving care" extended across Brazil and the US. Brazil emphasized the need for task-shifting and -sharing amongst health care disciplines, whereas the US suggested specialized approaches geared toward increasing access to toxicologists and other referral resources. Despite similar core barriers to adequate snakebite envenoming care and factors to consider when trying to improve care delivery, health professionals in different health systems and sociocultural contexts identified different needs. Accounting for, and understanding, these differences is crucial to the success of initiatives intended to strengthen snakebite envenoming care. Implementation science efforts, with explicit health professional input, should be applied to develop new and/or adapt existing evidence-based treatments and practices for SBE. Graphical abstract: Image 1 Highlights: Most deaths and permanent disabilities from snakebites are preventable. Implementing effective treatment across different contexts is challenging. Health providers in different contexts identified different care needs. Differences were 1) system level, 2) actor responsible, and 3) care delivery model. Understanding sociocultural and resources differences is essential.